IMPLEMENTING VERTICAL GREENERY ON OFFICE FAÇADE OPENING TO IMPROVE INDOOR LIGHT QUALITY - Luciana Kristanto; Sri Nastiti Nugrahani Ekasiwi; Asri Dinapradipta (DIMENSI (Journal of Architecture and Built Environment), 2022)
In medium-rise office building on tropical climate, façade fenestration mostly dominated by glass curtain wall. In this case, an effort should be done to control the daylight penetration and to shade glare of low sun angle especially from west orientation. The idea is utilized the vertical greenery system (VGS) on facade opening, how it performs as glare limitation as well as accommodating view. Firstly, the variable of artificial shading to light parameter are studied. Then, the previous research of VGS were explored, to find its influential variables. The last step was developed recommendation of VGS implementation on office facade opening to improve light quality. Finding from the study, the most influential variables are the plant species suitable to the climate condition, its canopy leaves area as light variable, and the placement; an integration the plants construction system with other facade elements which consider light angles of incidence and viewer’s sightlines.